The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1986
DOI: 10.1002/arch.940030204
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Brush border fragments from mosquito mesenterons

Abstract: Brush border fragments were isolated from homogenates of mesenterons from the mosquito, Culex tarsalis, by a combination of Ca2+ precipitation and differential centrifugation. These preparations were routinely enriched seven-to eightfold for the brush border marker enzyme, leucine aminopeptidase. Alkaline phosphatase, a putative brush border marker for both vertebrate and invertebrate brush borders, was found to be unsuitable for Cx. tarsalis. lsoelectric focusing electrophoresis coupled with histochemical enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 33 publications
(54 reference statements)
1
16
0
Order By: Relevance
“…Electron microscopy of insect midgut microvilli preparations (Houk et al 1986, Santos et al 1986) demonstrates, as previously observed for vertebrate enterocytes (Schmitz et al 1973), that they are substantially free from other cell structures, although the microvilli still contain some cytoskeleton elements. The amount of contaminating membranes is evaluated with marker enzymes.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Electron microscopy of insect midgut microvilli preparations (Houk et al 1986, Santos et al 1986) demonstrates, as previously observed for vertebrate enterocytes (Schmitz et al 1973), that they are substantially free from other cell structures, although the microvilli still contain some cytoskeleton elements. The amount of contaminating membranes is evaluated with marker enzymes.…”
supporting
confidence: 59%
“…Early attempts to study the biochemistry of microvillar membranes consisted on the determination of the ratio of phosphorus to protein content in microvilli preparations from Lepidoptera larvae and SDS-PAGE of these proteins (Wolfersberger et al 1987) and in similar preparations from Diptera adults (Houk et al 1986). Nevertheless, as discussed above, microvillar membranes are contaminated by cytoskeleton elements and other minor components.…”
Section: Biochemistry Of Microvillar Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation was obtained from fresh or frozen whole larvae (1-3 g wet mass), stored without buffer at -80°C. The protocol was developed from previously described techniques by means of selective divalent-cation precipitations (Biber et al, 1981;Houk et al, 1986;Nielsen-LeRoux and Charles, 1992) and differential centrifugations of brush-border membranes in ice-cold 0.3 M mannitol, 5 mM EGTA, 20 mM Tris/HCl, pH 7.5. The protocol is shown schematically in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…aegypti larvae following methods modified from those of Biber et al (1981;described in Wolfersberger et al, 1987) and Houk et al (1986). Fourthinstar larvae were chilled on ice, midguts extruded by dissection under a binocular microscope, peritrophic membranes and malpighian tubules removed, and midguts rinsed in icecold buffer A (0.3 M mannitol/5 mM EGTAj20 mM Tris/ HCl, pH 7.4).…”
Section: Brush-border Membrane Isolationmentioning
confidence: 99%